Il “ridere” come rottura nelle cornici di senso: esplorazione filosofica a partire da un chiasma platonico (Itinera, 2013)
The chiastic nexus between Socrates’ irony and its ridiculousness in the eyes of Thrasymachus permits to reformulate the importance of laughter as an ambiguity-laden philosophical subject. Taking into account the functions attributed to laughter by many authors – particularly Plato, Bergson, Kant, and Plessner – this paper investigates the relationship among laughter, approval, and displeasure, suggesting that the ambiguity of laughter comes out from a temporary breakdown either in the consolidated frames of meaning, or in the attempts to suggest new ones.